2016
DOI: 10.1016/j.sbi.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Filament assemblies in foreign nucleic acid sensors

Abstract: Summary Helical filamentous assembly is ubiquitous in biology, but was only recently realized to be broadly employed in the innate immune system of vertebrates. Accumulating evidence suggests that the filamentous assemblies and helical oligomerization play important roles in detection of foreign nucleic acids and activation of the signaling pathways to produce antiviral and inflammatory mediators. In this review, we focus on the helical assemblies observed in the signaling pathways of RIG-I-like receptors (RLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 100 publications
1
65
0
Order By: Relevance
“…The autorepressed 2CARD is liberated when dsRNA binds the helicase and C-terminal domains (Hel-CTD) of RIG-I (26,27), although ATP binding was also proposed to be important (25,28). Multiple studies showed that a release of 2CARD is not sufficient for MAVS activation; it additionally requires a tetramerization of 2CARD (29). At least two non-mutually exclusive mechanisms have been proposed to stimulate 2CARD tetramerization.…”
Section: Rig-i-like Receptorsmentioning
confidence: 99%
“…The autorepressed 2CARD is liberated when dsRNA binds the helicase and C-terminal domains (Hel-CTD) of RIG-I (26,27), although ATP binding was also proposed to be important (25,28). Multiple studies showed that a release of 2CARD is not sufficient for MAVS activation; it additionally requires a tetramerization of 2CARD (29). At least two non-mutually exclusive mechanisms have been proposed to stimulate 2CARD tetramerization.…”
Section: Rig-i-like Receptorsmentioning
confidence: 99%
“…Previous structural and biochemical studies have revealed a detailed picture of how RIG-I recognizes dsRNA with 5'ppp and how viral RNA binding leads to signal activation (Lassig and Hopfner, 2017;Rawling and Pyle, 2014;Sohn and Hur, 2016). In the absence of viral RNA, RIG-I is in an auto-repressed state wherein the signaling domain, the N-terminal tandem CARD (2CARD), is inhibited from activating MAVS (Kowalinski et al, 2011).…”
Section: Effective Immune Response To Viral Infection Depends On the mentioning
confidence: 99%
“…RIGā€I and MDA5 share a similar domain organisation. Recognition of an RNA substrate by the Cā€terminal domain (CTD) of RIGā€I or MDA5 leads to structural rearrangements that are transmitted via the conserved helicase domain and allow the two Nā€terminal caspase activation and recruitment domains (CARDs) to trigger oligomerisation of the adaptor MAVS (mitochondrial antiviral signalling) on the mitochondrial membrane, which in turn leads to IRFā€3, IRFā€7 and NFā€ĪŗB activation, nuclear translocation and IFN gene transcription (Goubau etĀ al , 2013; Wu & Chen, 2014; Sohn & Hur, 2016). Whilst RIGā€I recognises 5ā€²diā€ or triā€phosphates at the baseā€paired extremities of viral RNA, MDA5 and LGP2 recognise long doubleā€stranded RNA (dsRNA), the precise features of which are less wellā€defined (Hornung etĀ al , 2006; Kato etĀ al , 2006; Pichlmair etĀ al , 2006, 2009; Goubau etĀ al , 2014).…”
Section: Introductionmentioning
confidence: 99%